2020
DOI: 10.1186/s12944-020-01301-y
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet altered cardiac metabolic gene profile in Psammomys obesus gerbils

Abstract: Background: In metabolic disorders, myocardial fatty infiltration is critically associated with lipotoxic cardiomyopathy. Methods: Twenty Psammomys obesus gerbils were randomly assigned to normal plant or high fat diet. Sixteen weeks later, myocardium was sampled for pathobiological evaluation. Results: A sixteen-week high fat diet resulted in myocardial structure disorganization, with collagen deposits, lipid accumulation, cardiomyocyte apoptosis and inflammatory cell infiltration. Myocardial expressions of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
2
2
0
1
Order By: Relevance
“…A similar composition was reported for the Chenopodiaceae plant, Salsola foetida , with an EV of 0.4 kcal/g [ 38 ], S. bigelovii, with an EV of 0.3 kcal/g [ 31 ], and S. herbaceae with an EV of 0.44 kcal/g [ 43 ]. The determined EV of HCD is also similar to that used in similar experiments varying from ~3.70 kcal/g [ 38 , 44 ] to ~4.00 kcal/g [ 41 , 45 ].…”
Section: Resultssupporting
confidence: 62%
“…A similar composition was reported for the Chenopodiaceae plant, Salsola foetida , with an EV of 0.4 kcal/g [ 38 ], S. bigelovii, with an EV of 0.3 kcal/g [ 31 ], and S. herbaceae with an EV of 0.44 kcal/g [ 43 ]. The determined EV of HCD is also similar to that used in similar experiments varying from ~3.70 kcal/g [ 38 , 44 ] to ~4.00 kcal/g [ 41 , 45 ].…”
Section: Resultssupporting
confidence: 62%
“…It should be noted that the highest hypertrophic lesions were observed in the SFA-fed animals, whereas the lowest were found in the group of mice fed a diet with the n-6/n-3 PUFA ratio of 5:1. As previously described and partially confirmed in our study, high fat diets rich in SFA [ 22 , 23 , 24 ] or diets based on equal proportions of SFA, MUFA, and PUFA [ 25 ] induced the development of cardiac hypertrophy and intravascular fibrosis. Additionally, excess dietary linoleic acid (LA) has also been related to increased collagen deposition in the left ventricle in C57BL/6 mice [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…The two gerbil species focused on in this study have also been reported to become obese and exhibit metabolic abnormalities when maintained on a standard laboratory diet or a high fat diet, although not in the wild [23,25,49,50]. For example, sand rat islet cells show more pancreatic β-cell damage compared to rat islets when exposed to high glucose concentrations, and even healthy sand rats on plant-based diets do not have a strong response to human insulin [51,52].…”
Section: Discussionmentioning
confidence: 96%